Impact of hypofractionated and standard fractionated chemoradiation before pancreatoduodenectomy for pancreatic ductal adenocarcinoma. Issue 17 (31st May 2016) - Cloyd, Jordan M.; Crane, Christopher H.; Koay, Eugene J.; Das, Prajnan; Krishnan, Sunil; Prakash, Laura; Snyder, Rebecca A.; Varadhachary, Gauri R.; Wolff, Robert A.; Javle, Milind; Shroff, Rachna T.; Fogelman, David; et al.
Abstract : BACKGROUND: Previous studies have suggested that preoperative chemoradiation (CRT) is associated with an improved margin‐negative resection rate among patients who undergo pancreatoduodenectomy (PD) for pancreatic ductal adenocarcinoma (PDAC). However, the optimal preoperative regimen has not been established. METHODS: All patients with PDAC who received chemotherapy and/or CRT followed by PD between 1999 and 2014 were retrospectively reviewed. The effects of 2 external‐beam radiation regimens—a standard course of 50.4 Gy in 28 fractions and a hypofractionated course of 30 Gy in 10 fractions—were compared. Differences in clinicopathologic characteristics, locoregional recurrence (LR), and overall survival (OS) were assessed. RESULTS: Among 472 patients who received preoperative therapy, 224 (47.5%) received 30 Gy, 221 (46.8%) received 50.4 Gy, and 27 (5.7%) received chemotherapy alone. Patients who received 50.4 Gy were more likely to have advanced‐stage disease and to have received induction and postoperative chemotherapy, but there was no difference in the R1 margin status, treatment effect, LR, or OS between the 2 radiation groups (all P values > .05). Patients who received preoperative CRT had a lower rate of LR than patients who received preoperative chemotherapy alone ( P < .01). In a multivariate Cox proportional hazards analysis, 50.4 Gy was associated with OS and LR similar to those associated with 30 Gy, whereas the absence of preoperative radiation was associated with a higher rate of LR (odds ratio, 2.21; 95% confidence interval, 1.04‐4.70) and similar OS. CONCLUSIONS: Preoperative hypofractionated CRT was associated with similar local control and OS in comparison with standard CRT in patients undergoing PD for PDAC. The use of chemotherapy alone without CRT was associated with poorer local control but similar survival. Cancer 2016 . © 2016 American Cancer Society . Cancer 2016;122:2671–2679. © 2016 American Cancer Society. Abstract : In this single‐institution review of patients undergoing preoperative therapy before pancreatoduodenectomy for pancreatic ductal adenocarcinoma, the administration of hypofractionated chemoradiation is associated with margin‐negative resection rates, treatment effect, locoregional recurrence, and overall survival similar to those associated with standard fractionated chemoradiation. The use of either preoperative chemoradiation regimen is associated with improved locoregional control (but not overall survival) in comparison with systemic chemotherapy alone.